2007
DOI: 10.1215/15228517-2007-026
|View full text |Cite
|
Sign up to set email alerts
|

Early recurrences in histologically benign/grade I meningiomas are associated with large tumors and coexistence of monosomy 14 and del(1p36) in the ancestral tumor cell clone

Abstract: Tumor recurrence is the major clinical complication in meningiomas, and its prediction in histologically benign/grade I tumors remains a challenge. In this study, we analyzed the prognostic value of specific chromosomal abnormalities and the genetic heterogeneity of the tumor, together with other clinicobiological disease features, for predicting early relapses in histologically benign/grade I meningiomas. A total of 149 consecutive histologically benign/grade I meningiomas in patients who underwent complete t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 47 publications
5
62
0
Order By: Relevance
“…2 There is no clear explanation, however, as to why the majority of recurrent meningiomas derive from benign histology even after apparently radical removal. 55 Other attempts to classify meningiomas have used genomic techniques to study their genesis and progres sion, 73 as well as to search for genetic mutations and variable gene expression mediated via epigenetic modi fications. 35 The use of epigenomics as a clinical tool has become better understood in recent years 47 and research has started to elucidate the importance of epigenetics in meningioma progression.…”
mentioning
confidence: 99%
“…2 There is no clear explanation, however, as to why the majority of recurrent meningiomas derive from benign histology even after apparently radical removal. 55 Other attempts to classify meningiomas have used genomic techniques to study their genesis and progres sion, 73 as well as to search for genetic mutations and variable gene expression mediated via epigenetic modi fications. 35 The use of epigenomics as a clinical tool has become better understood in recent years 47 and research has started to elucidate the importance of epigenetics in meningioma progression.…”
mentioning
confidence: 99%
“…Recently, we have shown that meningioma patients with monosomy 14 and del(1p36), together with a larger tumour size, have a higher probability of relapsing during the first 2.5 years after diagnostic surgery. 10 Interestingly, in our study, all except two cases with the complete loss of chromosome 14 also displayed del(1p36) in the ancestral tumour cell clone (Table 1) and these latter patients included the two cases who had relapsed. Previous studies 1,11,36 have defined a few regions (eg, 14q24.3-q32.33 and 14q11.2) as critical regions in chromosome 14 where candidate genes involved in determining the clinical behaviour of meningiomas could be localized.…”
Section: Discussionmentioning
confidence: 60%
“…From the clinical point of view, chromosome 14 loss has been associated with a shorter recurrence-free survival, independently of tumour histopathology, particularly when detected in all tumour cells in the sample (eg, in the ancestral tumour cell clone) in association with del(1p36). 3,9,10,25 Altogether, these results suggest the presence of one or more tumour suppressor genes in this chromosome. Despite this, few studies have been reported so far in which a more precise characterization of the genetic changes involving chromosome 14, aimed at a better understanding of the clinical behaviour of the tumour, have been analysed.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Many studies confirmed the importance of tumour localisation, proliferative markers like Ki-67, the type of tumour resection and also the specific genetic alterations, for the risk of neoplasm recurrences [1,6,17,18].…”
Section: Discussionmentioning
confidence: 93%